Identification of SNAT Family Genes Suggests GhSNAT3D Functional Reponse to Melatonin Synthesis Under Salinity Stress in Cotton - Zhang, Yuexin; Rui, Cun; Fan, Yapeng; Xu, Nan; Zhang, Hong; Wang, Jing; Sun, Liangqing; Dai, Maohua; Ni, Kesong; Chen, Xiugui; Lu, Xuke; Wang, Delong; et al. (Frontiers in Molecular Biosciences, 2022)
Serotonin N-acetyltransferase (SNAT) is a key enzyme in the biosynthesis of melatonin, and plays an important role in the regulation of melatonin synthesis. The study of SNAT is of great significance to understand the function of melatonin. In this study, we analyzed the structural characteristics, phylogenetic relationship, gene structure, expression pattern, evolutionary relationship and stress response of the members of the SNAT gene family in upland cotton through bioinformatics, identified a putative Serotonin n-acetyltransferase gene GhSNAT3D, and preliminarily verified the function of GhSNAT3D by virus-induced gene silencing. We identified a total of 52 SNAT genes in the whole genome of G. hirsutum, and part of the GhSNATs were regulated by exogenous melatonin. The content of melatonin, antioxidant enzyme activity and Ca2+ content of GhSNAT3D gene silenced plants decreased, and the salt tolerance of GhSNAT3D gene silenced plants was reduced. Exogenous melatonin supplementation restored the salt tolerance of GhSNAT3D gene silenced plants. GhSNAT3D may interact with GhSNAT25D and ASMT to regulate melatonin synthesis. This study provided an important basis for further study on the regulation of melatonin in cotton against abiotic stress.